The Effect of Various of Example-Based Learning on Learning Achievement and Satisfaction in Educational Statistics Courses - Muhidin, Aeng; Wibawa, Basuki; Khaerudin, Khaerudin; Doriza, Shinta (FKIP Universitas Lampung, 2024)
Example-based learning has been studied from different perspectives. Cognitive research has mainly focused on worked examples, which typically provide students with a written worked-out didactical solution to a problem to study. Social-cognitive research has mostly focused on modeling examples, which provide students the opportunity to observe an adult or a peer model performing the task. The present study aims to compare university students’ performance and satisfaction in various example-based learning. It involves paper-based examples (PBE), video-based examples (VBE) and mixed-based examples (MBE). An experimental study was administered with the participation of 36 undergraduate students who are enrolled in their third-year studies at a private university in Banten, Indonesia. The study findings reveal that MBE is superior in promoting students’ performance and satisfaction in example-based learning. It can be concluded that MBE stimulates higher learning performance and satisfaction. These findings complement previous studies with additional insight into learning satisfaction. Due to the focus of this study and the tendency of previous studies which were mainly experimental, it is recommended for conducting narrative studies in the future to disclose detailed performance and satisfaction per individual case. Keywords: educational statistic, example based learning, satisfaction, learning performance.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp878-892